(untitled) (American Journal of Research in Humanities and Social Sciences, 2022)
This article focuses on the unique demographic situation of the population of Fergana Valley, and provides information on the impact of demographic processes such as population growth, birth, death, marriage, divorce on the socio-economic situation of the valley regions.